Colonization and Antibiotic Resistance of Nasal Staphylococcus Aureus among Healthcare Workers in Southwestern Iran: Occurrence of OS-MRSA - Abbas Abdollahi; Zahra Montaseri; Seyed Saeid Yazdanparast; Maryam Montaseri (Fasa University of Medical Sciences, 2022)
Background & Objectives: Staphylococcus spp. is a resident flora of the skin and mucosa of humans that can colonize the anterior nares of individuals. This cross-sectional study was conducted to determine the rate and antibiotic resistance pattern of nasal Staphylococcus aureus (S. aureus) carriers among the staff of Fasa hospital, southern Iran. Materials & Methods: Nasal swab samples were collected from 117 hospital staff working in 12 wards. Microbiological culture method was applied for S. aureus identification. The isolates were confirmed by tuf gene identification using PCR assay. Five isolates were randomly sequenced and phylogenetically analysed  using MEGA software. The antimicrobial resistance pattern of the isolates was evaluated using the disc diffusion assay and the amplification of the methicillin resistance (mecA) gene. Results: The prevalence of S. aureus nasal carriers included 10.26% (n=12). The nasal carriers were identified in the wards of surgery ICU, gynecologic surgery, NICU, pediatric, internal surgery, and emergency. Among them, gynecologic surgery staff had the highest rate of nasal colonization (33.33%). Phylogenetic analysis showed that of five isolates, four had high similarities with each other. Also, the highest rate of resistance was related to penicillin (83.3%), followed by cefazolin (75%), and cephalexin (75%). However, the highest level of susceptibility (100%) was found for vancomycin, cefoxitin, and oxacillin. Furthermore, the methicillin resistance gene (mecA) was highly detected (75%) from the isolates, elucidating oxacillin-susceptible or cefoxitin-susceptible mecA-positive S. aureus (OS-MRSA). Conclusions: The high rates of OS-MRSA can lead to antibiotic resistance among health care workers tremendously. Moreover, the high similarity probability in phylogenetic analysis shows the possibility of cross-infection between these health care workers, warning to exert effective strategies to control infection spread, especially in the surgery ward.